The favorite-longshot bias and the impact of experience - Eberhard Feess; Helge Müller; Christoph Schumacher (Business Research, 2014)
With a unique data set from New Zealand which allows us to assign each bet to individual bettors, we analyze the impact of experience on behavior and success in non-parimutuel (fixed odds) sports betting markets. We find that experienced bettors bet more on favorites than inexperienced bettors do. Average returns, which we use as success measure, increase with experience even after controlling for odds. This means that the higher return of experienced bettors cannot only be attributed to betting more on favorites. To get a more detailed picture, we divide the data set into ten equally large subgroups, sorted by experience. We find that odds decrease from subgroup to subgroup, while success consistently increases. This shows that the positive impact of experience is not mainly driven by professional bettors.
Keywords: D14; D81; G11; 330; Behavioral economics; Behavioral finance; Favorite-longshot bias; Betting markets; Learning in financial markets